Peningkatan Kemampuan Motorik Halus Anak Melalui Kegiatan Menempel di Kelompok Bermain - Abarua, Hermelina (Guidance and Counseling Study Program, Pattimura University, 2017)
Childhood is the most crisis period in the growth and development of human life both in terms of physical and emotional. At this time the child's character begins to be formed and will continue to grow and will be attached to him to adulthood. Therefore, since the early child needs to be taught character education and life skills are right so that someday the child becomes a qualified human being independent and good moral. In early childhood learning should be packaged in the form of games according to the age of the child, early childhood is the age of play, therefore, learning situations, procurement and organizing learning means should be designed for learning activities while playing. (Life-oriented Life Skills Guidelines). The problem that we face in KB Mawar FKIP Unpatti is the lack of children's room to play and the children's play facilities are very limited / minimal, so that the motor lesson and motor lesson in children less than the maximum. This study aims to identify and describe matters related to improving the fine motor ability of children in the learning process through attached activities in KB Mawar FKIP Unpatti Ambon. This research is a Classroom Action Research. The subjects of this study were students of KB Mawar FKIP Unpatti Ambon, amounting to 18 people. Data collection techniques are observation, interview, field note and documentation study. This classroom action research procedure is carried out in two cycles, namely cycle I and cycle II. The results showed that in the first cycle, there are still students who do not meet the criteria of the indicators conducted by the tutor, so it can be said as a weakness encountered in the implementation of the first cycle action, while in cycle II students are very active to hear the teacher explanation. Very active in question is that students can follow the teacher's explanation well so that what is assigned can be done well. Thus it can be concluded that with the sticking activity can improve the fine motor skills of early childhood in KB Mawar FKIP Unpatti Ambon.